TMEM16F/Anoctamin 6 in Ferroptotic Cell Death - Ousingsawat, Jiraporn (Cancers (Basel), 2019)
Ca(2+) activated Cl(−) channels (TMEM16A; ANO1) support cell proliferation and cancer growth. Expression of TMEM16A is strongly enhanced in different types of malignomas. In contrast, TMEM16F (ANO6) operates as a Ca(2+) activated chloride/nonselective ion channel and scrambles membrane phospholipids to expose phosphatidylserine at the cell surface. Both phospholipid scrambling and cell swelling induced through activation of nonselective ion currents appear to destabilize the plasma membrane thereby causing cell death. There is growing evidence that activation of TMEM16F contributes to various forms of regulated cell death. In the present study, we demonstrate that ferroptotic cell death, occurring during peroxidation of plasma membrane phospholipids activates TMEM16F. Ferroptosis was induced by erastin, an inhibitor of the cystine-glutamate antiporter and RSL3, an inhibitor of glutathione peroxidase 4 (GPX4). Cell death was largely reduced in the intestinal epithelium, and in peritoneal macrophages isolated from mice with tissue-specific knockout of TMEM16F. We show that TMEM16F is activated during erastin and RSL3-induced ferroptosis. In contrast, inhibition of ferroptosis by ferrostatin-1 and by inhibitors of TMEM16F block TMEM16F currents and inhibit cell death. We conclude that activation of TMEM16F is a crucial component during ferroptotic cell death, a finding that may be useful to induce cell death in cancer cells.